I need help please!!!
![I need help please class=](https://us-static.z-dn.net/files/dfc/a2cfa258e1fd4c6c24d653e28d1214af.png)
Part 1
---------------------
Explanation:
We'll replace every copy of x with -3. Then use PEMDAS to simplify.
f(x) = -2x+7
f(-3) = -2(-3)+7
f(-3) = 6+7
f(-3) = 13
===========================================================
Part 2
---------------------
Explanation:
We work backwards in a sense compared to what part 1 did. Instead of finding f(x) based on x, we determine what x must be for a given f(x).
We'll replace f(x) with 29 and solve for x like so
f(x) = -2x+7
29 = -2x+7
-2x+7 = 29
-2x = 29-7
-2x = 22
x = 22/(-2)
x = -11
Note how if you replaced x with -11, we'd get,
f(x) = -2x+7
f(-11) = -2(-11)+7
f(-11) = 22+7
f(-11) = 29
which helps confirm we have the correct answer.